Design, Development, and User Acceptance Evaluation of the “Trigosolver” Trigonometry Educational Game using the Unity Engine and the Agile Method - Zainul Arham; Yusuf Durachman; Hikam Rizqillah Munandar; Nur Aeni Hidayah; Nia Kumaladewi (Universitas Islam Indragiri, 2026)
Mathematics, particularly trigonometry, is often perceived by high school students as abstract and difficult to understand due to the complex spatial visualization it requires. Conventional teacher-centered instruction, which primarily emphasizes memorizing formulas, frequently fails to foster a strong conceptual understanding, resulting in low student motivation. This study aims to design, develop, and evaluate an interactive educational game called TrigoSolver as an alternative learning medium for trigonometry. The application was developed using the Unity Engine with the C# programming language and the Agile (Scrum) software development methodology, which supports iterative and adaptive development. The game incorporates a Pythagorean Triples algorithm based on Euclid's formula to dynamically generate trigonometry problems through Procedural Content Generation (PCG) while avoiding irrational numbers. It also includes an automatic fraction-answer validation feature to improve the learning experience. The system was evaluated through Black Box Testing to verify functional correctness and a User Acceptance Test (UAT) using a Likert-scale questionnaire developed based on the ISO/IEC 25010 software quality standard and the Technology Acceptance Model (TAM). The Black Box Testing results confirmed that all game functionalities operated as intended without errors. The UAT, involving seven subject-matter and media experts, yielded an overall feasibility score of 82.57% (classified as